Improving the Regional Economy with Integrated Activities Import Export, Warehousing, Integration Transport Systems, and Logistic Distribution: Perspective Review - Fasida Dharma Yudastoro (Formosa Journal of Sustainable Research, 2023)
This scientific article wants to provide a reinforcement and justify qualitatively about the variables used from reputation journals.  Scientific articles with qualitative methods by searching literature from scientific articles from reputable journals and then made a summary by researchers with a researcher's perspective.  Regional economy with variables with imports and exports there is an influence and positive from two scientific articles found with  different research objects from international journals found, both regional economies with distribution there are two articles that state to have the influence of variables and positive, other variables regional economy with logistic distribution,   Warehousing did not find scientific articles with research results that stated positive or significant influences but stated that the results of research with qualitative methods with explanations of the perspective of each researcher